Family Characteristics, Food Security, Expenditure, and Dietary Diversity among Families with and without Concurrently Wasted and Stunted Children in Semarang - Rachma Purwanti; Ignasia Agatha Br Ginting; Nurhanna Putri Aulia; Nuryanto Nuryanto; Fillah Fithra Dieny (Amerta Nutrition)
Background: Family characteristics, food security, expenditure, and diversity are indirectly associated with children's nutritional status.